2018
DOI: 10.1002/pen.24834
|View full text |Cite
|
Sign up to set email alerts
|

A novel chitosan gels: Supercritical CO2 drying and impregnation with thymol

Abstract: Supercritical carbon dioxide (scCO 2 ) technology was used for preparation of functional pH sensitive chitosan-based aerogels characterized with micron size pores and their impregnation with thymol as a natural bioactive substance. Hydrogels based on chitosan, itaconic and methacrylic acids were transformed to alcogels and dried in the air or with scCO 2 to obtain xero-and aerogels, respectively. Applying 10 min of static and 120 min of dynamic scCO 2 drying at 11 MPa and 458C followed with the decompression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 51 publications
0
16
0
1
Order By: Relevance
“…Thymol and other essential oil molecules have been impregnated into various matrices using scCO 2 . 30,31 The solubility of thymol was investigated by Milovanovic et al at different pressures and temperatures. Consequently, they performed the impregnation on cotton gauzes at 35°C and 155 bars which conferred antimicrobial properties to the material.…”
Section: Introductionmentioning
confidence: 99%
“…Thymol and other essential oil molecules have been impregnated into various matrices using scCO 2 . 30,31 The solubility of thymol was investigated by Milovanovic et al at different pressures and temperatures. Consequently, they performed the impregnation on cotton gauzes at 35°C and 155 bars which conferred antimicrobial properties to the material.…”
Section: Introductionmentioning
confidence: 99%
“…[216] Ag nanoparticles also act as antibacterial additives. [217] Chitosan-biopolymer composites are proposed for biomedical scaffolds,e ither as wet cryogels or as freeze-dried gels: [218] Gelatin-agarose,a lginate,c ollagen, caprolactone, carrageenan, chondroitin sulfate,h yaluronic acid, cellulose, cyclodextrin, polylactide and poly(lactic-co-glycolic acid), polyglutamic acid, pectin, silk fibroin, starch, and chitin are typical biopolymers for this purpose,s ometimes combined with HAp and TCP to modify mechanical properties.Scaffold functionalization with polymers and macromolecules is also am ajor topic, for example,w ith DNA, [219] peptides, [220] nucleoside diphosphates, [221] and enzymes [222] for delivery and sensing applications,w ith polypyrrole [223] and polyaniline [224] for electrical conductivity,a nd with polyacrylamides, [225] polyethylene glycol, [226] polyvinyl alcohol, [227] polymethyl methacrylate, [228] and polyethylenimine [229] for improving mechanical properties and other functions.Carbon-based materials,s uch as graphene oxide, [230] carbon nanotubes, [231] and carbon black, [232] are also suitable components for electrical conduction and sensing applications.…”
Section: Compositesmentioning
confidence: 99%
“…Terzić et al [58] applied scCO 2 technology to the preparation of functional pH-sensitive chitosan-itaconic acid-methacrylic acid (Ch/IA/MAA) aerogels characterized with micron-size pores and their impregnation with thymol. Ch/IA/MAA hydrogels were obtained first, transferred to alcogels, and then dried in air to obtain xerogel or in scCO 2 to obtain aerogels.…”
Section: Impregnation Of Polymeric Forms Other Than Textiles and Fibersmentioning
confidence: 99%
“…The scCO 2 drying consisting of 10 min of static and 120 min of dynamic drying at 11 MPa and 45 • C followed by the decompression at a rate of 1 MPa/min resulted in an advantageous aerogel with favorable swelling kinetics and elasticity, compared to the xerogel and aerogels obtained at other decompression rates and drying times. The aerogel was subsequently loaded with thymol (up to 4.6 wt.%) in a batch SSI process at 10 MPa and 35 • C with the impregnation time of up 5 h. In vitro studies of swelling in phosphate buffered saline (PBS) at 37 • C indicated a considerable potential of the obtained stimuli-responsive gel for topical administration of thymol [58].…”
Section: Impregnation Of Polymeric Forms Other Than Textiles and Fibersmentioning
confidence: 99%